CORRELATION STUDIES FOR GRAIN YIELD AND ITS COMPONENTS IN HYBRIDS OF QUALITY PROTEIN MAIZE (Zea mays L.) - S. VANI SREE, PANDURANG ARSODE, K. MURALI KRISHNA, N. SUNIL and (The Journal of Research, PJTSAU, 2019)
Maize is the third most important cereal crop after wheat and rice and is considered one of the most versatile emerging crop having wider adaptability under varied agro-climatic conditions. During 2015- 16, globally maize was cultivated on an area of 178 million ha in about 160 countries with a total production of 1037 million tons (Foreign Agricultural Service, USDA, 2016). In India, the crop was grown on 9.2 million ha with a total production of 26.15 million metric tons and an average yield of 3340 kg/ha. In Telangana state, it covers an area of 0.69 million hectares with a production of 2.31 million tonnes and productivity of 3340 kg ha-1 (India Stat, 2015).